Options for Improved Treatment of Saline Wastewater From Fish and Shellfish Processing - Anh, Hoang Thi Hong; Shahsavari, Esmaeil; Bott, Nathan J.; Ball, Andrew S. (Frontiers in Environmental Science, 2021)
The rapid growth of the aquaculture industry over recent decades, with annual production reaching 94.6 million tonnes in 2018 has resulted in a significant increase in saline wastewater following the use of seawater in both fish and shellfish production and processing. This wastewater contains high concentrations of nutrients, organic compounds, and total nitrogen, resulting in the requirement for significant treatment prior to discharge to meet environmental regulations, which are becoming more stringent. The infrastructure and running costs associated with physico-chemical treatment approaches are generally higher than the implementation of biological approaches; the latter represents both an economic and sustainable technology. However, salinity represents a significant inhibitor to microbial activity, affecting the efficacy of the biological treatment of wastewater. This review aims to 1) identify the major biodegradable components in saline fish wastewater that may result in deleterious effects upon discharge, 2) discuss the current methods used for the treatment of fish processing wastewaters, and 3) identify opportunities for improved processes to be utilised and identify gaps in knowledge that require further research. Total suspended solids (TSS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), and total nitrogen (TN) were found to be the most prevalent components in fish effluent. High concentrations of TSS and TN are likely due to the protein content. One method for reducing the environmental impact of the treated wastewater is to enhance nutrient removal (TSS, TN, BOD) through process modification, leading to an increase in active proteolytic activity. Bioaugmentation using immobilised, saline-tolerant proteases or halophilic, protease-producing microorganisms have both shown significant potential in laboratory studies in reducing both the COD and TN content of fish processing wastewater to below discharge limits and therefore may represent commercial options for future treatment processes.